A biocompatible photosensitizer with a high intersystem crossing efficiency for precise two-photon photodynamic therapy. Issue 4 (16th February 2022) - Xu, Zhourui; Jiang, Yihang; Shen, Yuanyuan; Tang, Lele; Hu, Zulu; Lin, Guimiao; Law, Wing-Cheung; Ma, Mingze; Dong, Biqin; Yong, Ken-Tye; Xu, Gaixia; Tao, Ye; et al.
Abstract : A biocompatible organic room-temperature phosphorescence photosensitizer that can be excited using two-photon near-infrared light is developed for photodynamic therapy to achieve improved oxygen species generation and tissue penetration. Abstract : Photodynamic efficiency is strongly dependent on the generation rate of reactive oxygen species (ROS) and the tissue penetration depth. Recent advances in materials science reveal that organic molecules with room-temperature phosphorescence (RTP) can potentially serve as efficient photosensitizers owing to their limited dark cytotoxicity and abundant triplet excitons upon light irradiation. In this study, we combine RTP materials with two-photon excitation to improve the ROS generation, therapeutic precision, and tissue penetration of photodynamic therapy. We successfully prepared a novel RTP-based photosensitizer (BF2 DCz) with a high photoluminescence quantum yield of 47.7 ± 3% and a remarkable intersystem crossing efficiency of ∼90.3%. By encapsulation into the bovine serum albumin (BSA) matrix, BF2 DCz-BSA exhibits excellent biocompatibility, negligible dark toxicity, and superior photostability. Excitation using a femtosecond laser causes BF2DCz-BSA to efficiently generate ROS and precisely exert cell damage at the desired location.